2011
DOI: 10.1073/pnas.1018091108
|View full text |Cite
|
Sign up to set email alerts
|

Targeting zebrafish and murine pituitary corticotroph tumors with a cyclin-dependent kinase (CDK) inhibitor

Abstract: Cushing disease caused by adrenocorticotropin (ACTH)-secreting pituitary adenomas leads to hypercortisolemia predisposing to diabetes, hypertension, osteoporosis, central obesity, cardiovascular morbidity, and increased mortality. There is no effective pituitary targeted pharmacotherapy for Cushing disease. Here, we generated germline transgenic zebrafish with overexpression of pituitary tumor transforming gene (PTTG/securin) targeted to the adenohypophyseal proopiomelanocortin (POMC) lineage, which recapitula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 43 publications
3
98
0
Order By: Relevance
“…3). The results indicate that use of selective CDK inhibitors may effectively target corticotrope tumor growth and hormonal secretion (Liu et al 2011b). (Amaral et al 2009).…”
Section: Cell Cycle Regulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). The results indicate that use of selective CDK inhibitors may effectively target corticotrope tumor growth and hormonal secretion (Liu et al 2011b). (Amaral et al 2009).…”
Section: Cell Cycle Regulatorsmentioning
confidence: 99%
“…The leading effect of such pathways is cell cycle arrest with a decrease in tumor growth. Interestingly, using a cyclindependent kinase 2 (CDK2)/cyclin E inhibitor in animal models, the ACTH and corticosterone levels were suppressed, and xenografted pituitary tumor growth was restrained (Liu et al 2011b). Red lines/arrows indicate inhibition, whereas green lines/arrows indicate induction.…”
Section: Peroxisome Proliferator-activated Receptor Gamma Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of p27/kip1 function leads to the development of PAs (60). Furthermore, Liu et al (61) found that a selective inhibitor of CDK markedly suppressed ACTH levels and restrained growth of ACTH-secreting PAs in mice. One study revealed that germline CDKN1B mutations rendered individuals more susceptible to MEN1 (62).…”
Section: Leukemia Inhibitory Factor (Lif) Mutation and Cyclin-dependementioning
confidence: 99%
“…A single zebrafish model for pituitary corticotroph adenoma has been described. 67 In this model, overexpression of the pituitary tumor transforming gene (pttg/securin) in cells of the adenohypophyseal proopiomelanocortin (POMC) lineage leads to formation of pituitary corticotroph adenomas in adult transgenic zebrafish. 67 Interestingly, adult transgenic zebrafish developed multiple signs of endocrine dysfunction, including hypercortisolemia, hyperplasia of renal steroidogenic cells, relative insulin resistance, hepatic lipidosis, and cardiomyopathy.…”
Section: Models Of Neural and Neuroendocrine Neoplasiamentioning
confidence: 99%